The yellow fever epidemic in the port of Callao during 1868 - Inga Rumiche, Sally (2019)
In the second half of the nineteenth century, the fertilizing properties of guano were rediscovered, in order to extract this product it was necessary to have labor, which encouraged the migration of Chinese workers to Peru. When their arrival coincided with the appearance of yellow fever, the prejudice was formed that they had introduced the disease to the country through miasmas. When a strong yellow fever epidemic broke out at the beginning of 1868, the Peruvian State put into practice a series of policies that sought to curb the advance of evil, these policies were applied with great emphasis on the Puerto del Callao, due to the fact that here anchored ships with Asian crew, which made it a powerful source of infection. These policies consisted, for example, of passing inspection to ships arriving at the port, and in the case of any of these suspects of carrying the disease, send them to quarantine to San Lorenzo Island. Despite the precautions taken, they did not have the expected effect, since they did not counteract the root of the problem (the disease is caused by the bite of the Aedes aegypti mosquito) due to scientific ignorance. Thus generating a series of erroneous prejudices towards Chinese immigrants. To develop this work three parts will be addressed, in the first one a description of the economic situation and the process of Chinese immigration will be made, in the second part the introduction of yellow fever in the Port of Callao will be described and finally in the third The main measures taken by the State to stop the spread of yellow fever will also be developed, as well as prejudices towards Chinese residents.